Issues Most Important to Parents After Their Children's Suicide Attempt: A Pilot Delphi Study. Issue 4 (16th October 2015) - Hickey, Kari; Rossetti, Jeanette; Strom, Jan; Bryant, Kelly
Abstract : Problem: Suicide is the third leading cause of death for people aged 15–24 and results in 4, 600 lives lost each year. One important risk factor for completed suicide is a nonlethal suicide attempt. To date, little research has been conducted on the needs of parents of adolescents who have made a nonlethal suicide attempt. Methods: The goal of this pilot study was to describe the most important concerns of parents whose children have made a nonlethal suicide attempt from the perspective of adolescent mental health professionals. A two‐round Delphi technique was utilized with an interdisciplinary panel of adolescent mental health experts to gain consensus on what issues are most important to parents after their children's suicide attempt. Findings: Panelists described the following as most important to parents after their children's nonlethal suicide attempt: keeping their children safe; identifying what caused or triggered the suicide attempt; strategies to prevent another suicide attempt; and communication and building trust for the future. Conclusions: An advanced understanding of the issues most important to parents whose children have made a nonlethal suicide attempt has implications for clinicians in creating acceptable and useful interventions aimed at preventing youth suicide.